CHARACTERIZATION OF PHYSICAL AND CELLULAR PROPERTIES OF MEMBRANES OF L-PRF PRODUCED BY DIFFERENT CENTRIFUGES/ CENTRIFUGATION PROTOCOLS. - Palmeira Esteves Schleinstein, Camilla; de Freitas, André Carlos; Palmeira da Silva , Viviane; de Santana Cerqueira, Naiadja; Teixeira Cangussu, Maria Cristina; Pedreira Ramalho, Luciana Maria (Brazilian Journal of Implantology and Health Sciences, 2024)
Leukocyte and platelet-rich fibrin (L-PRF), an essential source of cytokines and growth factors, has been widely used to regulate the healing process. The quality of the L-PRF obtained is dependent on technical factors and the centrifugation protocol used. Thus, the present study aimed to macro and microscopically evaluate the formation of the L-PRF membrane/clot in two centrifuge models and protocols recommended by manufacturers. Four blood samples from 8 healthy volunteers undergoing rehabilitation surgery with dental implants were used. In group 1 of the Montserrat centrifuge (model 80-2B 15mL) 400g of centrifugal force were used for 10 minutes, 27ºC, and 2700 rpm, while in group 2 of the Intra Spin-Intra-Lock centrifuge (IntraSpin™, Intra-Lock Iberia) 400g of centrifugal force were used for 12 minutes, 27ºC and 2700 rpm. After obtaining 32 L-PRF clots/membranes, the pieces were recorded, measured, and weighed, separating the L-PRF from the supernatant/clot of red blood cells, remaining in the tubes. The specimens were then histologically processed for Hematoxylin/Eosin (H/E) staining and each slide was divided into three called areas: proximal, center, and distal. The presence of leukocytes was analyzed semi-quantitatively in each area. The results revealed no significant macroscopic differences in L-PRF between the two groups. However, the central areas of the L-PRF membranes produced in group 2 showed higher intensity of leukocytes (p=0.012), as well as the presence of concomitant leukocytes in at least 2 of the evaluated areas (p=0.003). In the proximal area, no significant differences were observed between the two groups. The results allow us to postulate that technical protocol factors influence the presence and distribution of leukocytes between the L-PRF membranes, obtained in different centrifuges.